MODEL MENTAL MISKONSEPSI PADA KONSEP KESETIMBANGAN KELARUTAN - Chusnur Rahmi; Wiji Wiji; Sri Mulyani (UIN AR-RANIRY, 2020)
Study on students' mental model's analysis was done to identify misconceptions about solubility equilibria concept. The method employed in the study was a case study uses a qualitative approach. The participants were 23 students of class XI of a senior high school in Bandung. The instrument used in the study was the Diagnostic Test on Mental Model-Prediction, Observation, Explanation (TDM-POE). The results showed that there were diverse of students' misconceptions about the precipitate formation of a reaction, the effect of common ions and decrease in pH on solubility. Based on the results of the study, many misconceptions occur in the subconcept of the effect of common ions on solubility. Misconceptions arise because students have incomplete mental models at the submicroscopic level.